2011
DOI: 10.1002/pro.601
|View full text |Cite
|
Sign up to set email alerts
|

Binding of small molecules to cavity forming mutants of a de novo designed protein

Abstract: A central goal of protein design is to devise novel proteins for applications in biotechnology and medicine. Many applications, including those focused on sensing and catalysis will require proteins that recognize and bind to small molecules. Here, we show that stably folded a-helical proteins isolated from a binary patterned library of designed sequences can be mutated to produce binding sites capable of binding a range of small aromatic compounds. Specifically, we mutated two phenylalanine side chains to ala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…Two relatively large pockets (volumes: 205 and 174 Å 3 ), comprised of Leu30, Met33, Asn34, Met37, His74, and Leu75 (in chain A/B) and Leu16, Leu19, Phe85, Leu89, and Leu92 (in chain B/A) are detected using the programs Pocket-Finder () and Cavor () (Figure ). Similar sized pockets were also found in the F64A mutant of monomeric protein S-824 . We hypothesize that these hydrophobic pockets may serve as substrate binding sites.…”
Section: Resultssupporting
confidence: 68%
“…Two relatively large pockets (volumes: 205 and 174 Å 3 ), comprised of Leu30, Met33, Asn34, Met37, His74, and Leu75 (in chain A/B) and Leu16, Leu19, Phe85, Leu89, and Leu92 (in chain B/A) are detected using the programs Pocket-Finder () and Cavor () (Figure ). Similar sized pockets were also found in the F64A mutant of monomeric protein S-824 . We hypothesize that these hydrophobic pockets may serve as substrate binding sites.…”
Section: Resultssupporting
confidence: 68%
“…To confirm binding and estimate affinities, we used pulse field gradient spin echo (PFGSE) NMR (21). This method is well-suited to study the affinities between macromolecules and SMs, and we have used it previously to study binding to novel proteins (22). PFGSE NMR enables estimation of binding affinities from the mole fraction of the protein/ligand complex, which is estimated from the observed diffusion coefficients of the ligand in the free and bound states.…”
Section: Resultsmentioning
confidence: 99%
“…21 This method is well-suited to study the affinities between macromolecules and SMs, and we have used it previously to study binding to novel proteins. 22 PFGSE NMR enables estimation of binding affinities from the mole fraction of the protein/ligand complex, which is estimated from the observed diffusion coefficients of the ligand in the free and bound states. PFGSE experiments monitoring the interaction of paromomycin with S836 and S23 yielded K D values in the range of 15−20 μM (Figure 4a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We have used the binary code strategy to design several libraries of α‐helical and β‐sheet proteins, and have demonstrated that proteins from the α‐helical libraries fold into well‐ordered stable structures . Proteins from these libraries bind small molecules, including cofactors, and catalyze reactions . Most importantly, several of these de novo α‐helical proteins function in vivo to provide essential activities necessary to sustain the growth of living cells …”
Section: Introductionmentioning
confidence: 99%